(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examined the relationship between audit committee characteristics and bank’s financial, operational and market performance. The study used a pooled data of Banks listed on the Gulf Cooperation Council Stock Exchange during the period from 2015 to 2019. The study independent variable is audit committee characteristics. Also the study utilized bank specific and macroeconomic control variables in order to help measuring the relationship between audit committee characteristics and bank’s Performance. Multiple regression approach was incorporated under Fixed-effect method. The findings showed that the Audit committee member’s financial expertise has negatively influenced the ROA and ROE of Islamic and conventional banks. Moreover, the size of audit committee and the AC member’s independency in Islamic banks has positive significant impact on TQ models and the audit committee meeting is significantly affecting the ROA and ROE model. However, in conventional banks the independency of audit committee and the audit committee meetings have positive significant impact on ROA, ROE and TQ models.